Het Krinkzinnegen te Buitenzorg: Perkembangan Dalam Melayani Kesehatan Jiwa (1882-1966) - Gartika, Erni; Martini, Sri; Djunadi (PERIODE: Jurnal Sejarah dan Pendidikan Sejarah, 2023)
Abstract: ERNI GARTIKA. HET KRINKZINNEGEN TE BUITENZORG: DEVELOPMENTS IN THE SERVICE OF MENTAL HEALTH (1882-1966). History Education Study Program, Faculty of Social Sciences, Jakarta State University. 2023. The purpose of this study is to find out how the development of mental health care in this mental hospital from the colonial period to the beginning of Orde Baru. The method used in this study is a historical method with a descriptive narrative model consisting of source collection (heuristics), source criticism (verification), interpretation, and writing (historiography). The results of this study show that advances in the health sector, especially mental health in the Netherlands, also have an impact on colonies, including the Dutch East Indies. In addition, the increase in people with mental disorders in the population in the Dutch East Indies was also the cause of the establishment of a Mental Hospital where previously people with mental disorders were accommodated in the Army Hospital or even in prison. The establishment of a Mental Hospital in Dutch East Indies became then the city of Bogor was chosen to be the place where the first Mental Hospital in the Dutch East Indies was established, namely Krinkzinnegen te Buitenzorg. That way, of course, Krinkzinnegen te Buitenzorg is an important part of the mental health scene in Indonesia. This mental hospital is one of the clear evidence of the long history of mental health in Indonesia to date. Bogor Mental Hospital has undergone several developments and updates. Development both in facilities and infrastructure, where the development in a better direction is by humanizing patients with mental disorders. Keywords: Development, Krinkzinnegen te Buitenzorg, Mental Hospital, Mental Health Abstrak: ERNI GARTIKA. HET KRINKZINNEGEN TE BUITENZORG: PERKEMBANGAN DALAM MELAYANI KESEHATAN JIWA (1882-1966). Program Studi Pendidikan Sejarah, Fakultas Ilmu Sosial, Universitas Negeri Jakarta. 2023. Tujuan Penelitian ini untuk mengetahui bagaimana perkembangan perawatan kesehatan jiwa di Rumah Sakit jiwa ini dari masa colonial hingga orde lama. Metode yang digunakan dalam penelitian ini adalah metode historis dengan model deskriptif naratif yang terdiri dari pengumpulan sumber (heuristik), kritik sumber (verifikasi), interpretasi (penafsiran) dan penulisan (historiografi). Hasil Penelitian ini menujukan bahwa kemajuan bidang kesehatan khususnya kesehatan jiwa di Belanda berdampak pula pada tanah jajahan termasuk Hindia Belanda. Selain itu peningkatan pengidap gangguan jiwa pada penduduk di Hindia Belanda juga menjadi penyebab didirikannya Rumah Sakit Jiwa dimana sebelumnya penderita gangguan jiwa ditampumg di Rumah Sakit Tentara atau bahkan di penjara. Pendirian Rumah Sakit Jiwa di Hindia Belanda menjadi Lalu dipilihlah kota Bogor menjadi tempat berdirinya Rumah Sakit Jiwa pertama di Hindia Belanda yaitu Krinkzinnegen te Buitenzorg. Dengan begitu tentunya Krinkzinnegen te Buitenzorg menjadi bagian penting dalam kancah kesehatan jiwa di Indonesia. Rumah Sakit Jiwa ini menjadi salah satu bukti nyata dari sejarah panjang kesehatan jiwa di Indonesia hingga saat ini. Rumah Sakit Jiwa Bogor mengalami beberapa perkembangan dan pembaharuan. Perkembangan baik secara sarana maupun prasarana, dimana perkembangan ke arah yang lebih baik yaitu dengan lebih memanusiakan pasien dengan gangguan jiwa. Kata Kunci: Perkembangan, Krinkzinnegen te Buitenzorg, Rumah Sakit Jiwa, Kesehatan Jiwa